Capacity to Consent of People with Dementia: a Narrative Review from an Ethical Perspective - Urfa Khairatun Hisan; Nurul Qomariyah; Kristina Elizabeth (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
People with dementia have impairment to execute daily life activities by presenting as a deterioration of mental processes, such as memory, thinking, reasoning, and judgment. Many participants in dementia research may lack the capacity to provide informed consent. Additional safeguards are needed for dementia research participants’ protection because of their vulnerability. Only after carefully weighing the risks and possible benefits for the participants in the research may it be decided to use vulnerable participants. The intention to prevent harm pushes against the removal of autonomy. This dilemma is the driving force behind this article's narrative review of the capacity to consent problems in dementia research. For this critical narrative review, we conducted a thorough search of Scopus, PubMed, and Wiley Open Library for literature addressing the ethical and legal issues on the capacity to consent of people with dementia. We outline the dilemmas and difficulties that surround them including the related ethical principles, the informed consent process, capacity to consent, and safeguards for the participant in research involving people with dementia.